Remote sensing of wetland types: Tropical flooded forests - Hess, Laura; Costa, Maycira; Evans, Teresa; Silva, Thiago S.F. [UNESP]; Chapman, Bruce; Milne, Tony (Springer Nature, 2018)
In many tropical regions, wetlands are extensive and are often associated with forested environments. Notable examples include those occurring in the floodplains of the Amazon and Congo Rivers. In these regions, cloud cover is prevalent and wetland mapping approaches have been most successful when using time series of Synthetic Aperture Radar (SAR) data. The description of wetlands in forested environments is particularly enhanced when using temporal L-band HH datasets. The provision of information on these tropical wetlands is leading to a better understanding of their contributions to regional and global climate, particularly given their important role as a repository for carbon.
Keywords: Carbon; Inundation; Synthetic aperture radar (SAR); Tropical wetlands